AIoT-Based Soil Moisture Monitoring System for Precision Agriculture and Energy Efficiency in Rural Smart Villages - Mandasari, R Deasy; Adrian, Ronald; Kustiawan, Iwan; Alam, Sahirul; Lukman Hakim, Dadang; Wahyudin, Didin (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Alamendah Village is a horticultural area where irrigation and energy use are still managed manually, leading to water inefficiency and unmonitored electricity consumption. This study developed an AIoT-based system using ESP32 microcontrollers and soil moisture sensors to support precision irrigation and energy monitoring. The system design included sensor calibration to convert ADC values into moisture percentages, threshold-based irrigation recommendations, and a placement formula to determine sensor deployment. Field testing in strawberry plots demonstrated that soil moisture often dropped below the 40% threshold, triggering timely irrigation alerts. The dashboard provided real-time data visualization and revealed peak electricity demand in the evening at the village hall. The results indicated that the system enhanced irrigation accuracy, provided a baseline for monitoring energy consumption, and increased community awareness of sustainable resource management. The project offers a replicable model for integrating smart agriculture and energy monitoring in rural areas.